Self-dual toric varieties - Bourel, Matías (2011)
Let T be a torus over an algebraically closed field k of characteristic 0, and consider a projective T -module P ( V ). We determine when a projective toric subvariety X ⊂ P ( V ) is self-dual, in terms of the configuration of weights of V.